Effects of particulate contamination and jet fuel chemistry on the nucleation of water and ice in aircraft fuel systems - Ugbeh, Judith (Cranfield University, 2018)
3MT presented at the 2018 Defence and Security Doctoral Symposium.The contamination and behaviour of water in aircraft fuel systems remains a significant area of global research interest following several aircraft incidents. Water and particulates in fuel may lead to ice formation. The resulting ice formed may eventually block the fuel filters and feed pipes creating safety problems.In order to engineer a lasting solution to the problem of ice in jet fuel it is important to identify precisely the conditions and features that may exacerbate this phenomenon.This work will give a detailed account of the recent advances and technologies in the literature indicating conditions that might lead to the nucleation of water and ice in aircraft fuel systems. It will develop awareness of the key complexities associated with jet fuel chemistry. Furthermore, the work identifies the significant knowledge gaps that exist in the literature highlighting routes to be investigated for future research.
Keywords: 'Jet Fuel'; 'Nucelation'; 'Water Ice'; 'Aircraft Fuel Systems'; 'Crystallisation'; 'DSDS18 3MT'; 'DSDS18'; 'Non-automotive Combustion and Fuel Engineering (incl. Alternative/Renewable Fuels)'; 'Aerospace Engineering not elsewhere classified'